1976
DOI: 10.1111/j.1439-0329.1976.tb00533.x
|View full text |Cite
|
Sign up to set email alerts
|

Some observations on the longevity of Fomes annosus in conifer stumps.

Abstract: The longevity of Fomes annosus in conifer stumps was assessed in 3 investigations, which showed that the fungus could remain active in stumps for periods of 16 to 62 years.The important role of the stump in the biology of Fomes annosus was clearly demonstrated by RiSHiiiiTH (1950RiSHiiiiTH ( , 1951. During 3 recent investigations we have obtained information on the longevity of F. annosus in eonifer stumps, whieh has an important bearing on the danger of infeetion in subsequent conifer crops.1. In 24, second-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 4 publications
1
22
0
2
Order By: Relevance
“…Statistically significant values at the 95% level are indicated by (?) for clustering, and (•) indicates a pattern not significantly different from spatial randomness n is the number of trees analysed Oecologia (2010Oecologia ( ) 164:1107Oecologia ( -1119Oecologia ( 1113 Notably, pathogens that cause increased damage in trees predisposed by stress are often already present in their host before the stressful event (Greig and Pratt 1976;Franklin et al 1987;Manion 1991). The large size of some H. abietinum genets found in the study area suggests that they are more than 20 years old (Sánchez et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Statistically significant values at the 95% level are indicated by (?) for clustering, and (•) indicates a pattern not significantly different from spatial randomness n is the number of trees analysed Oecologia (2010Oecologia ( ) 164:1107Oecologia ( -1119Oecologia ( 1113 Notably, pathogens that cause increased damage in trees predisposed by stress are often already present in their host before the stressful event (Greig and Pratt 1976;Franklin et al 1987;Manion 1991). The large size of some H. abietinum genets found in the study area suggests that they are more than 20 years old (Sánchez et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Greig and Pratt (1976) showed that Heterobasidion is able to survive in stumps for decades. They found active pathogen's mycelium in 33-62-year-old Scots pine stumps, 30-46-year old larch and 30-year-old Douglas fir stumps, Norway and Sitka spruce.…”
Section: Resultsmentioning
confidence: 99%
“…Once H. irregulare is established in a pine stump, it can use grafts between infected and non-infected roots to further its spread within a plantation. Depending on pine species and geographical locations, H. annosum in Europe (Woodward et al 1998), which is very similar to H. irregulare, can survive in stumps for 10 to 46 yr (Redfern and Stenlid 1998), even up to 62 yr (Greig and Pratt 1976), thus making it a chronic infectious agent through several silvicultural treatments.…”
Section: Découvrir La Revuementioning
confidence: 99%